Environmental impacts on walleye pollock (Gadus chalcogrammus) distribution across the Bering Sea shelf. (December 2020) - Eisner, Lisa B.; Zuenko, Yury I.; Basyuk, Eugene O.; Britt, Lyle L.; Duffy-Anderson, Janet T.; Kotwicki, Stan; Ladd, Carol; Cheng, Wei
Abstract: Adult and juvenile (age-1) walleye pollock ( Gadus chalcogrammus ) were sampled by the US NOAA Alaska Fisheries Science Center summer bottom trawl survey in 2010, 2017, 2018, and 2019 in the northeastern and southeastern Bering Sea, with profiles of temperature collected concurrently. Similarly, the Russian Research Institute of Fisheries and Oceanography, Pacific branch, collected adult and juvenile pollock and temperature profiles on summer bottom trawl surveys in the northwestern Bering Sea. Results from these surveys show that adult pollock abundance in recent years (2017, 2018, 2019) has increased in northern regions of the Bering Sea shelf in both the US and Russian sectors. Lower abundances, compared to historic means, were observed in southern regions of the shelf, suggesting the pollock moved directionally from the south to the north. We relate changes in pollock distribution in recent intermediate (2017) and warm, low-ice years (2018–2019) to a prior cold, high-ice year (2010) and describe how these observations relate to our longer time series. We link temperature data from bottom trawl surveys (US and Russian), sea-ice indices (retreat timing and extent), as well as model-based estimates of ocean circulation to changes in pollock distribution and examine potential environmental factors driving the observed changes. Changes in sea-ice and bottom temperature (e.g., reductions in ice extent and shrinking of the cold pool), and changes in circulation (stronger northward currents over the northeastern shelf in warmer years, particularly in 2018) led to changes in distributions of adult and age-1 pollock. Adult pollock were concentrated north of St. Lawrence Island and had larger longitudinal distributions in warm years, 2017–2019; whereas they had a more southerly and narrow distribution over the outer shelf in the cold year, 2010. Age-1 pollock had higher densities over the inner eastern shelf in 2017–2019 compared to 2010. Northward flow around St. Lawrence Island (particularly in the spring) alternated between stronger flow on the west side of the island in 2010 and 2017 and stronger flow on the east side of the island in 2018 and 2019; variations in flow may have impacted the location of prey and movement of feeding pollock to the Chukchi Sea. Size structure comparisons between NW, NE and SE sections of the Bering Sea shelf suggest that movement of fish between US and Russian waters may have been highest in 2019, one of the two warmest years, and lowest in 2010, the coldest year. Spatial comparisons of distributions and size structure across the Bering Sea help provide a comprehensive view of factors affecting the movement of this highly important commercial fish species. Highlights: Adult walleye pollock moved farther north in the Bering Sea in warm years, 2017–2019. Pollock distributions relate to reductions in sea-ice, cold pool extent and currents. Adult pollock prefer temperatures of 0–6 °C; age-1pollock tolerate a broader range. Continued warming presents possibility of US–Russia stock mixing. US–Russia collaborations are key to understanding climate impacts on fisheries.